Validation of previously reported predictors for radiation-induced hypothyroidism in nasopharyngeal cancer patients treated with intensity-modulated radiation therapy, a post hoc analysis from a Phase III randomized trial. (10th May 2018) - Lertbutsayanukul, Chawalit; Kitpanit, Sarin; Prayongrat, Anussara; Kannarunimit, Danita; Netsawang, Buntipa; Chakkabat, Chakkapong
Abstract: This study aimed to validate previously reported dosimetric parameters, including thyroid volume, mean dose, and percentage thyroid volume, receiving at least 40, 45 and 50 Gy (V40, V45 and V50), absolute thyroid volume spared (VS) from 45, 50 and 60 Gy (VS45, VS50 and VS60), and clinical factors affecting the development of radiation-induced hypothyroidism (RHT). A post hoc analysis was performed in 178 euthyroid nasopharyngeal cancer (NPC) patients from a Phase III study comparing sequential versus simultaneous-integrated boost intensity-modulated radiation therapy. RHT was determined by increased thyroid-stimulating hormone (TSH) with or without reduced free thyroxin, regardless of symptoms. The median follow-up time was 42.5 months. The 1-, 2- and 3-year freedom from RHT rates were 78.4%, 56.4% and 43.4%, respectively. The median latency period was 21 months. The thyroid gland received a median mean dose of 53.5 Gy. Female gender, smaller thyroid volume, higher pretreatment TSH level (≥1.55 μU/ml) and VS60 < 10 cm 3 were significantly associated with RHT in univariate analyses. Only pretreatment TSH ≥ 1.55 μU/ml and VS60 < 10 cm 3 were significant predictors in multivariate analysis. Our results suggested that patients with pretreatment TSH ≥ 1.55 μU/ml should be cautious about the risk of RHT. The VS60 ≥ 10 cm 3 is recommended for treatment planning.